2015
DOI: 10.1039/c4ra09033k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of new copper(i) based linear 1-D-coordination polymers with neutral imidazolinium-dithiocarboxylate ligands

Abstract: An imidazolinium-dithiocarboxylate betaine has been applied for the first time as a ligand in a coordination polymer with copper(i) halides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 86 publications
0
10
0
Order By: Relevance
“…The starting point for the preparation of [Cu 4 (Bz 2 ImCS 2 ) 4 Cl 2 ] 2+ ( 2 ) and [Cu 3 (Bz 2 ImCS 2 ) 5 ] 3+ ( 3 ) was the coordination polymer [CuCl(Bz 2 ImCS 2 ) 2 ] n ( 1 ), which is easily accessible in excellent yields and purity by reaction of CuCl with Bz 2 ImCS 2 in acetonitrile (Scheme ), as a solid with low solubility. A combined NMR spectroscopy and ESI‐MS study showed us that liquid phases obtained, after saturating MeCN with 1 and subsequent filtering, contain the mononuclear ions [Cu(Bz 2 ImCS 2 ) 2 ] + and [CuCl 2 ] – as the only copper‐containing species in solution.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The starting point for the preparation of [Cu 4 (Bz 2 ImCS 2 ) 4 Cl 2 ] 2+ ( 2 ) and [Cu 3 (Bz 2 ImCS 2 ) 5 ] 3+ ( 3 ) was the coordination polymer [CuCl(Bz 2 ImCS 2 ) 2 ] n ( 1 ), which is easily accessible in excellent yields and purity by reaction of CuCl with Bz 2 ImCS 2 in acetonitrile (Scheme ), as a solid with low solubility. A combined NMR spectroscopy and ESI‐MS study showed us that liquid phases obtained, after saturating MeCN with 1 and subsequent filtering, contain the mononuclear ions [Cu(Bz 2 ImCS 2 ) 2 ] + and [CuCl 2 ] – as the only copper‐containing species in solution.…”
Section: Resultsmentioning
confidence: 99%
“…The compound 1,3‐dibenzyl‐3‐imidazolinium‐2‐dithiocarboxylate (Bn 2 ImCS 2 ) was prepared according to the literature . The synthesis of the coordination polymer [CuCl(Bz 2 ImCS 2 )] n ( 1 ) was recently reported …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To verify whether the styryl group attached on poly(l-cysteine) can carry out the free radical polymerization and thiol-ene click reaction that are suitable methods to form a polypeptide networked polymers, [31][32][33][34] we first examined free radical polymerization to obtain a polypeptide network using the lowest molecular weight of PCys(VBn) ((M n : 1130, M w /M n = 1.20) in the presence of AIBN as a radical source (Scheme 4). After heating them in a nitrogen atmosphere for 24 h, an easily breakable and totally insoluble glassy solid polymer (Network-PCS) was obtained in high yield (90%), and their film formation was not observed.…”
Section: Resultsmentioning
confidence: 99%